2019
DOI: 10.3389/fvets.2019.00295
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Soybean Meal With Soybean Cake Reduces Methane Emissions in Dairy Cows and an Assessment of a Face-Mask Technique for Methane Measurement

Abstract: The objective of this study was to (a) evaluate the effect of replacing soybean meal (SBM) with soybean cake (SBC) on feeding behavior, rumen fermentation, milk production, nutrient digestibility and CH4 emissions and (b) investigate whether a face-mask technique could be used to predict daily methane (CH4) emissions in dairy cattle. The experiment was conducted as a completely randomized design, with 32 crossbred Holstein × Gyr cows (days in milk (DIM): 112 ± 25.1) randomly assigned to the following treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…The short-term (30 min/day for 3 days) facemask technique generated CH 4 measurements that were comparable to those estimated using SF 6 and RC across a range of dry matter intake levels in bulls [ 22 ]. It was also confirmed that the CH 4 emissions measured using the facemask technique were comparable to those measured by RC at the same time point (6 h after morning feeding, 30 min/day for 2 days) in dairy cattle [ 23 ].…”
Section: Measurement Techniquesmentioning
confidence: 60%
See 4 more Smart Citations
“…The short-term (30 min/day for 3 days) facemask technique generated CH 4 measurements that were comparable to those estimated using SF 6 and RC across a range of dry matter intake levels in bulls [ 22 ]. It was also confirmed that the CH 4 emissions measured using the facemask technique were comparable to those measured by RC at the same time point (6 h after morning feeding, 30 min/day for 2 days) in dairy cattle [ 23 ].…”
Section: Measurement Techniquesmentioning
confidence: 60%
“…A facemask is another technique using a similar mechanism of gas concentration analysis to that of a ventilated hood and RC but in a manner of spot sampling [ 22 , 23 ]. The mask fully covers the muzzle by a strap attached around the neck of the animal.…”
Section: Measurement Techniquesmentioning
confidence: 99%
See 3 more Smart Citations